Efeitos da dramatização sobre compreensão oral de histórias infantis por alunos com deficiência auditiva. - Carvalho, Vânia Lúcia Corradi (2004)
The scholar integration proposal demands that the school organize itself to facilitate the access for students with hearing impairment to the curriculum, allowing them, under those circumstances, to have educational opportunities to reach enough knowledge to perform their citizenship. The educational needs of these students demand effort of educators providing them a flexibility of the instruction resources, making feasible the opportunities of learning that take into account their singularity, especially related to communication. This paper had as the main objective an assessment to evaluate the effectiveness of the use of fairy tale dramatization, as an educational strategy to provide an improvement of the oral comprehension of stories for five students with hearing impairment, aged between 7 and 13, enrolled on a public school. It was used an experimental multiple baseline design between individuals, which started with an assessment of previous knowledge that each participant had; hearing impairment, previous knowledge about the fairy tale, followed by the participation of each one in a training with a pedagogical activity and in the end a dramatization related to the fairy tale. These activities were performed by each student in different moments, in a same group composed of four no-hearing-impairment participants. The data were collected by video and/or tape recordings. One statistical descriptive analysis was applied, by comparing the previous knowledge that each student with hearing impairment had about the fairy tale, before and after the achievement of both pedagogical activities and dramatization. The results showed that the participants who had been exposed to the two posterior interventions showed more improvement in performing the assessment tests of the fairy tale oral comprehension, as much in the evaluations accomplished after the introduction of the pedagogical support activity as after the dramatization activity. Although the two interventions had promoted improvement in this performance, there were differences in the magnitude of the change when it was compared with each individual among themselves, or in the student himself, the effect of the two strategies (pedagogical support and dramatization). The inter and intra-individual rate differences suggest that individuals benefited themselves in different ways when the two teaching strategies were used, and it seems to point toward that there is no superiority of one strategy over another, what implies the importance in diversifying the teaching instruction to fulfill the individual particularities in learning condition of students with hearing impairment.